The distribution of the economic activity in European region: identification of cluster - Fernando A. López; Ana M. Angulo; Jesús Mur; Andrés Artal Tur (European Regional Science Association (ERSA), 2011)
Agglomeration economies play an important role in the explanation of the development and regional growth. For this reason, there exists a growing interest in the analysis of standards of co-localisation of the economic activities. This topic has been dealt with from different approaches using a good number of technical statistics. Our proposal is to present some of the more well-known statistics usually used in epidemiology, with the objective of identifying spatial clusters of companies dedicated to the same economic activity. As such, this paper analyses the geographic distribution of economic activity throughout the Mediterranean to the smallest possible level of spatial integration (post code level). Firstly, by using exploratory analysis tools of spatial data we identify patterns of localisation of economic activity including both industrial and service areas. Secondly, by using the statistics of T. Tango (1995) and M. Kulldorff (1997) we identify clusters of businesses in distinct subsectors of activity. The information is obtained from the 'Sistema Anual de Balances Ibéricos' (SABI) database and using the National Classification of Economic Activities NCEA code to a 2 digit level. Our results highlight that great differences exist in the production geographic concentration in all sectors. Additionally, the results from our analysis also reveal that well defined groups exist within the economic sectors.
Keywords: 330